Peer tutors’ agency and emotions in tertiary English language education in Vietnam - Cuong Huy Pham; Nguyen Thien Duyen Ngo (JEELS (Journal of English Education and Linguistics Studies), 2025)
Peer support has been found to have significant impacts on language learning as a supplement to formal lessons at school. This study draws on the construct of agency to explore Vietnamese students’ self-regulation, awareness of the responsibility, sociocultural factors affecting peer tutoring, and the emotional experiences shaping their commitment. The participants include one junior and two senior students in the BA in English Language Teaching program who volunteered to support their peers in the General English Program at a private university. They were invited to respond to a narrative frame to reflect on their experiences and the critical incidents they encountered in peer tutoring. Findings show the participants’ ongoing exercise of agency entailing their self-regulation, awareness of responsibility toward working with peers, and sociocultural elements that determined their resilience and levels of enthusiasm. They also found peer tutoring rewarding to their cognitive and affective development in terms of expanding personal relationships, resolving peer conflicts, gaining practical insights, and enhancing linguistic confidence. This study contributes to understandings of peer tutors’ agency, emotions, and relational issues that inform curriculum developers and language teachers in providing students with hands-on opportunities for teaching practice.